Analisis Pemahaman tentang Riba dan Minat Menabung di Bank Syariah Masyarakat Perumahan Bukit Hijau Karawaci - Nur Jamaludin; Fithri Wulandari; Bagus Sugiarto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this study is to determine the effect of public understanding of usury on interest in saving in Islamic banks in Perumahan Bukit Hijau Karawaci RW 022. The method used is quantitative descriptive using Partial Least Square (PLS) or Smart PLS Version 3.0 analysis techniques with research instruments in the form of a questionnaire. Respondents in this study amounted to 60 people using purposive sampling technique. The results of this study indicate that the public understanding of the Perumahan Bukit Hijau Karawaci RW 022 community about usury is quite good but still needs to be improved. This is evidenced by the results of the analysis of the variable understanding of usury on interest in saving in Islamic banks obtained a p-value of 0.011 < 0.05. It can be concluded that the variable understanding of usury has a significant effect on interest in saving in Islamic banks. This research is expected to be able to contribute information to the understanding of usury, especially in the Perumahan Bukit Hijau Karawaci community so that it can help increase interest in saving in Islamic banks.